The teaching of psychology: essay in honor of Wilbert J. McKeachie and Charles L. Brewer - Edited by Stephen F. Davis and William Buskist Stephen F. Davis (Londo: Lawrence erlbaum associates, 2002)
The Teaching of Psychology is centered around the masterful work of two champions of the teaching of psychology, Wilbert J. McKeachie and Charles L. Brewer, in order to recognize their seminal contributions to the teaching of the discipline. The book's main goal is to provide comprehensive coverage and analysis of the basic philosophies, current issues, and the basic skills related to effective teaching in psychology. It transcends the typical "nuts and bolts" type books and includes such topics as teaching at small colleges versus a major university, teaching and course portfolios, the scholarship of teaching, what to expect early in a teaching career, and lifelong learning.
Includes author index and subject index.
Keywords: Teaching of psychology